2007
DOI: 10.1002/ejoc.200700301
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Versatility of Sulfur in C–C Bond Formation and Cleavage: Synthesis of ABC Taxoid Skeletons

Abstract: A practical and convenient five-step protocol is described to access the ABC ring system of Taxol by utilizing the versatility of the sulfur atom in its various oxidation states viz., condensation/Pummerer cyclization/coupling/annulation/fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Analytical chiral HPLC was performed on a Chiralcel OD-H column (250 mm x 4.6 mm, 5 μm particle size, 0.8 mL/min flow rate) obtained from Daicel Chemical Industries, Ltd. 1 (2-Bromocyclohex-1-enyl)methanol (9). [1,2] The allylic alcohol was synthesized according to a similar procedure. [3] To a solution of DMF (7.4 mL, 95.0 mmol, 3.0 equiv) in CHCl 3 (25 mL) was added PBr 3 (8.1 mL, 86.0 mmol, 2.7 equiv) dropwise at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical chiral HPLC was performed on a Chiralcel OD-H column (250 mm x 4.6 mm, 5 μm particle size, 0.8 mL/min flow rate) obtained from Daicel Chemical Industries, Ltd. 1 (2-Bromocyclohex-1-enyl)methanol (9). [1,2] The allylic alcohol was synthesized according to a similar procedure. [3] To a solution of DMF (7.4 mL, 95.0 mmol, 3.0 equiv) in CHCl 3 (25 mL) was added PBr 3 (8.1 mL, 86.0 mmol, 2.7 equiv) dropwise at 0 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In 1997, Little and co-workers 171 In 2007, Chavan and co-workers 172 reported an oxidative cleavage approach to the taxane skeleton from tetracyclic system (Scheme 38B). Thus, treatment of tetracyclic compound 274 in the presence of Pb(OAc) 4 resulted in an oxidative cleavage reaction to afford the ABC taxoid core 275 as an inseparable 1:1 mixture of exo/endo double-bond isomers.…”
Section: Oxidative Cleavagementioning
confidence: 99%
“…In this field, Kakiuchi and co-workers have performed an oxidative cleavage of the tetrasubstituted double bond in substrate 494 derived from 368 to give the bicyclic diketone 495 (Scheme ) . In their synthetic studies on taxoids, the groups of Chavan and Spitzner have reported closely related oxidative fragmentation reactions. Alternatively, in their approach to the same ring system, Toyota and Ihara have used a Grob fragmentation of the hydroxy tosylate 496 to prepare the desired product 497 , but the competitive formation of the oxetane 498 could not be avoided …”
Section: Bicyclo[321]octanes As Synthetic Intermediatesmentioning
confidence: 99%
“…In this field, Kakiuchi and co-workers have performed an oxidative cleavage of the tetrasubstituted double bond in substrate 494 derived from 368 to give the bicyclic diketone 495 (Scheme 165). 207 In their synthetic studies on taxoids, the groups of Chavan 269 and Spitzner 270 have reported closely related oxidative fragmentation reactions. Alternatively, in their approach to the same ring system, Toyota and Ihara have used a Grob fragmentation of Contemporaneously, Biju and Rao explored some interesting synthetic routes for the elaboration of polyquinanes and proposed the preparation of the diquinane product 504 by a lead tetraacetate-promoted, selective ring cleavage of diol 503 obtained from 236 (Scheme 167).…”
Section: Fragmentation To Seven-membered Ringsmentioning
confidence: 99%